[Sr4Cl2][Si3S9]: Ultrawide-bandgap salt-inclusion thiosilicate nonlinear optical material with unprecedented tri-polymerized [Si3S9] clusters. Issue 13 (14th March 2023) - Zhao, Chenyao; Wu, Kui; Xiao, Yan; Zhang, Bingbing; Yu, Haohai; Zhang, Huaijin
Abstract : Salt-inclusion NLO thiosilicate [Sr4 Cl2 ][Si3 S9 ] with an unprecedented tri-polymerized [Si3 S9 ] cluster shows a good balance between an ultrawide bandgap and large SHG response. Abstract : Adjusting the inherent incompatibility between a wide optical bandgap ( E g ) and strong second-harmonic-generation (SHG) response ( d ij ) has become an urgent challenge for the design and exploration of outstanding infrared nonlinear optical (IR NLO) materials. To address this, a new salt-inclusion thiosilicate, [Sr4 Cl2 ][Si3 S9 ], exhibiting the first discovered tri-polymerized [Si3 S9 ] clusters, was successfully designed and synthesized by combining the native performance advantages of halides and sulfides. Detailed experimental and theoretical investigations showed that the uniformly aligned [Si3 S9 ] functional groups could make a great contribution to the large phase-matching (PM) d ij (1.2 × AgGaS2 ), while the ionic salt enabled a positive blue-shift of the absorption edge to achieve the widest E g (4.22 eV) reported among all known NLO chalcohalides. Furthermore, [Sr4 Cl2 ][Si3 S9 ] is the first example showing a superior balance between E g > 4.0 eV and d ij > 1.0 × AgGaS2 in the PM chalcohalide system and could thus effectively eliminate the undesirable property incompatibility, indicating that salt-inclusion thiosilicates are potential research candidates for exploring ultrawide-bandgap IR SHG materials.